Coference on water pollution problems in europe : Vol. 3 (Thousand Oaks, Calif. : Sage Pub., 1961)
"Combating AIDS focuses on communication strategies that could mobilize political action, target high-risk groups, and overcome stigma. Communication can be widely effective both as a "sledgehammer" and a "scalpel". The authors describe and analyze advocacy strategies, culturally-engaging targeted and tailored responses, and the entertainment-education strategy, including the use of television and radio soap operas to engage audiences emotionally and create a forum for public debate and discussion." "Focusing on the work being carried out by individuals and organizations, this book humanizes the AIDs epidemic. Interesting, informative, and readable, it will be of interest to policy-makers, practitioners, and scholars in the fields of public health, communication and change, development studies, social work, and public policy."--BOOK JACKET.
Machine derived contents note: Part One: History Of The Aids Epidemic -- Vulnerability to the Epidemic -- The Poor -- The Weak and Vulnerable -- Stigma -- Era 1: Urban Beginnings -- The Nature of HIV -- Beginnings -- The CDC Cluster Study -- Patient Zero -- Costly Delays -- The San Francisco Experience -- Era 2: Breaking Out of High-Risk Populations -- Era 3: Interiorization -- AIDS Orphans -- The ABC Orphanage -- My Name is Non -- Commercial Sex Workers -- Part Two: Aids Advocacy And Policies -- The Unruly Policy Agenda for AIDS -- Nkosi Johnson at the 2000 Durban Conference -- Agenda-Setting for the Issue of AIDS -- The Media Agenda -- Randy Shilts: Chronicler of the Castro -- The Public Agenda -- The Policy Agenda -- The Role of Tragic Figures -- The Role of Champions -- Thailand: Success! -- Minister Mechai -- Condom King -- The Epidemic in Thailand -- Total Mobilization -- The 100 Percent Condom Program -- Sustainability of the Mechai Initiatives -- Cambodia -- India -- The AIDS Epidemic and Economic Development -- Beginnings of the AIDS Epidemic in India -- Initial Government Initiatives -- AIDS Control in Tamil Nadu -- Activating Agencies -- Kofi Annan: Crusader for AIDS -- Part Three: Aids Drugs -- What Are Anti-Retrovirals? -- Brazil: A Ray of Hope -- Brazil's Brave Policy -- The Controversy Over Patent Rights -- Drug Company Investment in R&D -- A Complicated Regimen -- President Mbeki's Opposition to the Anti-Retrovirals -- Duesberg's Dissent -- Zachie Achmat, AIDS Activist -- Mother-to-Child HIV Infection -- Doctors without Borders -- PWA's Pressures for Drugs in Thailand -- Yusuf Hamied's Price Revolution -- Price Slashing by Cipla -- The Arbitrary Price of Drugs -- Search for an AIDS Vaccine -- Nutrition, the First Line of Defense -- Herbal Treatments -- Indigenous Knowledge Systems -- Pimjai and the Don Kaew Community Health Project -- Herbal Remedy in Chinese Ruins -- Part Four: Targeting Unique Populations -- Targeting in San Francisco -- The STOP AIDS Program -- A Proliferation of Prevention Programs -- The Targeting Strategy -- Targeting Hotspots -- Intervening Upstream -- Program Effectiveness -- Homophily with Targeted Individuals -- Credibility of Peer Educators -- Communication Networks -- The Network Nature of HIV Transmission -- Harm Reduction Among Intravenous Drug Users -- The Opinion Leader Strategy -- Commercial Sex Workers -- Epicenter of the Epidemic - Mumbai -- The CHES Program - Chennai -- Kolkata's Empowered CSWs -- The Healthy Highways Project in India -- Learning to Think Like a Truck Driver -- Refocusing Through Formative Research -- Urban Slums -- Using the Internet -- Part Five: Cultural Strategies -- Communication Challenges to HIV//AIDS -- Biomedical Approach to Disease and Intervention -- Problems with the Biomedical Approach to Zambia -- Behaviour Change Models -- The Social and Cultural Construction of AIDS -- The UNAIDS Framework -- Culture as an Ally -- Taping the Strength of the Nguni Culture -- Culture as Enemy along Lake Victoria -- Individualistic Versus Collectivistic Cultures -- Use of Cultural Artifacts -- The Role of Spirituality -- A Spiritual Jihad on IADS in Uganda -- Coping with AIDS Spiritually -- Spirituality as an Enemy -- Community Approaches to HIV//AIDS Prevention -- The Community Cares - Cefran -- Creating Sexual Subjects Through Freirean Approaches -- A Pedagogy of HIV Prevention -- Safe Sex as `Play' -- The Power of Sports -- Part Six: Overcoming Stigma -- The Difficulty of Overcoming Stigma -- AIDS Stigma in India -- Stigma Is Everywhere -- ACT UP: Fighting Stigma -- The Nature of Stigma -- Why Is HIV//AIDS Stigmatized? -- Measuring Stigma -- Overcoming Stigma -- Breaking the Silence -- From the Personal-Private to the Public-Policy -- Part Seven: Entertainment-Education -- The Entertainment-Education Stategy -- The Rise of Entertainment-Education -- Why Entertainment-Education? -- From Private Closets to Public Discourse -- Key Elements in Creating Entertainment-Education -- The Values Grid -- Formative Evaluation Research -- Blunder in South Africa -- Theory-Based Message Design -- Multimedia Campaign Activities -- /f003Twende na Wakati/f001 versus HIV in Tanzania -- `Don't Be a Mkwaju!' -- Soul City in South Africa -- Founding Soul City -- Entertainment-Education and Soul City -- Soul City's Yearly Campaigns -- The Key Role of Research -- Raising Efficacy -- Costs and Reach -- Using Markers in Entertainment-Education Programs -- f003 Malahacao in Brazil -- Participatory E-E Approaches to Address HIV -- Artists Against AIDS in Brazil -- Community Street Theatre in Zimbabwee -- Nalamdana in India -- Culturally Shareable Entertainment-Education Programmes -- The Global Institutionalization of Entainment-Education BBC World Service Trust's India Initiative -- 'On the Edge': A Warrior Vanquishes the Demon -- PCI's Entertainment-Education Interventions -- Ushikwapo Shikamana in Kenya -- Ushikwapo Shikamana Comics -- Program Effects -- Part Eight: Monitoring And Evaluation -- Field Experiments -- The Opinion Leadership Field Experiment in Gay Bars -- The Field Experiment in Chennai -- The Field Experiment in Tanzania to Evaluate /f003Twende na Wakati -- A Quantitative Approach to HIV//AIDS Research -- Social Change Indicators -- Behaviour Surveillances Surveys in Tamil Nadu -- BSS Methodology -- Peer-Based Interventions -- Monitoring Through Information Technology -- A Qualitative Approach to HIV//AIDS Research -- Participatory Evaluation -- Using Participatory Tools in Uganda -- Harvesting Questions -- Media Monitoring of AIDS -- Part Nine: Lessons Learned About Combating Hiv//Aids -- Looking Backward -- Ignoring Culture -- Slow Political Action -- When the Lion Comes, Shout! -- Lack of Business Involvment -- Stigma -- Looking Forward -- Communication Strategy -- PWA Power -- Recognizing Heroes -- Programmatic Synergy -- Sorting Ethical Dilemmas -- Redefining the Problem.
Includes bibliographical references (p. 393-411) and index.
Keywords: AIDS (Disease) -- Prevention; Communication in medicine; Health behavior